2010
DOI: 10.1097/shk.0b013e3181ae8155
|View full text |Cite
|
Sign up to set email alerts
|

RON RECEPTOR TYROSINE KINASE NEGATIVELY REGULATES TNFα PRODUCTION IN ALVEOLAR MACROPHAGES BY INHIBITING NF-κB ACTIVITY AND ADAM17 PRODUCTION

Abstract: The Ron receptor tyrosine kinase plays a regulatory role in the inflammatory response to acute lung injury induced by intranasal administration of bacterial lipopolysaccharide (LPS). Previously, we have showen that mice with a targeted deletion of the tyrosine kinase (TK) signaling domain of the Ron receptor exhibited more severe lung injury in response to intranasal LPS administration as evidenced by increased leakage of albumin in the lungs and a greater thickening of the alveolar septae compared to wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…Consistent with these in vivo data, ex vivo LPS treatment of TKϪ/Ϫ BMDMs led to significant increases in TNF-␣, iNOS, and IL-6 expression compared with TKϩ/ϩ cells. These studies are in accord with numerous publications citing the macrophage-specific regulation of cytokines and iNOS expression by Ron in vivo and in vitro (23,28,29,34,43). Macrophages play a vital role in inflammation, and their activation status determines the repertoire of proinflammatory or anti-inflammatory cytokine production.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with these in vivo data, ex vivo LPS treatment of TKϪ/Ϫ BMDMs led to significant increases in TNF-␣, iNOS, and IL-6 expression compared with TKϩ/ϩ cells. These studies are in accord with numerous publications citing the macrophage-specific regulation of cytokines and iNOS expression by Ron in vivo and in vitro (23,28,29,34,43). Macrophages play a vital role in inflammation, and their activation status determines the repertoire of proinflammatory or anti-inflammatory cytokine production.…”
Section: Discussionsupporting
confidence: 85%
“…23,35 TAMs were reported to suppress anti-tumor CD8 + T-cell responses in a mouse model of prostate cancer via RON signaling. 35 On the other hand, RON can also attenuate inflammatory responses in alveolar macrophages and protect mice from mortality following lung injury, 30 suggesting potent control of the immune responses in a localized manner. Supporting this view, local expression of MSP by breast cancer cells has been shown to recruit TAMs and polarize them into an immunosuppressive phenotype, resulting in enhanced tumor growth in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the RON receptor inhibits LPS and cytokine-induced NF-κB activation in a variety of macrophage populations (6, 15, 16); however, the molecular targets of Ron downstream of TLR activation in primary macrophages have not been systematically addressed. In this report, we show that stimulation of primary peritoneal macrophages with MSP, the ligand for Ron, does not inhibit receptor proximal signaling events initiated by LPS stimulation of TLR4, but rather specifically inhibits the activation of IκB kinase (IKK) and its downstream targets by LPS.…”
Section: Introductionmentioning
confidence: 99%